(untitled) - Porcelli, Pasquale (Chicago, 1966)
The contents of this monograph represent about one-third of the material the author presents in a first-year graduate course in complex variables. The course evolved over several years and has for its goals a thorough grounding in analytic function theory, the acquaintance of the student with the frontiers of knowledge in certain areas in analysis, and the familiarization of the student with some of the literature, stressing both recent works and historical patterns.
Keywords: Functional analysis,Hàm phân tích